Metabolic safety of the etonogestrel contraceptive implant in healthy women over a 3-year period. (July 2016) - Villas-Boas, Jaqueline; Vilodre, Luiz C.; Malerba, Helena; Pontremoli Salcedo, Mila; Foresti Jiménez, Mirela; El Beitune, Patrícia
Abstract: Objective: To ascertain whether placement of the etonogestrel contraceptive implant induces significant changes in carbohydrate and lipid metabolism, as reflected by metabolic parameters, in healthy women. Study design: Prospective cohort study of 213 healthy patients who received etonogestrel implants. Weight, BMI, blood pressure and a comprehensive metabolic profile were assessed at baseline, 1, 2 and 3 years. In 21 of the 213 participants, AUC for glucose levels, fasting insulin levels at baseline and year 3 (immediately before implant removal), HOMA-IR score, and the QUICK index were assessed. Parameters were expressed as median and interquartile range. The Wilcoxon test and ANOVA were used for comparison of measurements after implant placement (significance level p < 0.05). Results: Median age was 26 years (range, 22–31.5). Results showed a trend toward increase of the variables weight (63.3–66.1) and BMI (24.7–25.7) and a decrease in TC (172–161.5), TG (75–69.5), and LDL (100.5–98.5) ( p > 0.05). Of the metabolic variables, FBG (85–88) and HDL (53–46) had significant differences ( p < 0.002). In the subgroup of 21 patients, there were reductions in insulin levels (9.65 vs. 8.4 mU/dL, p = 0.03), HOMA scores (2.06 vs. 1.75, p = 0.02), QUICK index (0.34 vs. 0.35, p = 0.03), TC (178 vs. 160 mg/dL, p = 0.001), HDL (51 vs. 46 mg/dL, p = 0.009), and LDL (110 vs. 100 mg/dL, p = 0.035). Conclusion: These results provide evidence of the metabolic safety of the ENG implant in healthy women over a 3-year period. Indeed, implant placement induces changes consistent with a lower risk of insulin resistance and dyslipidemia.